(untitled) (Heritage, 2022)
The reason for writing this paper is the (non) application of the Agreement on Succession Issues, especially its Annex G, which refers to private property and acquired rights. The authors analyzed the legal norms from a theoretical point of view, and then, by researching case law and analyzing the decisions made, they pointed out the (non) application of the ratified Agreement on Succession Issues. Respecting the assumed international obligations, valid international law, legality and justice, as well as the credibility of the European Union, it is necessary in practice to ensure more efficient and direct application of Annex "G" of the Agreement on Succession Issues which stipulates that SFRY successor states will protect private property. and acquired rights of citizens and other legal entities. Result of the author’s paper is the Platform for "Ending the War Period" on the territory of the former joint state of SFRY by implementing the ratified Agreement on Succession Issues with Annexes of "A - G" with special reference to Annex "G" Private property and acquired rights, as a convalidation enacted laws and their legal consequences. The aim of the paper is for the representatives of the states of the former SFRY to adopt the proposals of the future Declaration on the basis of the mentioned Platform, which the authors presented in the conclusion of the paper.